Experiences and personal-social dynamics of the elderly in natural settings: case study in Lingga Village, Indonesia - Nurman Achmad; Fotarisman Zaluchu (Cogent Arts & Humanities)
The increasing proportion of the elderly population presents a significant challenge for the future. It is projected that in a few decades, the number of elderly individuals will reach a highly significant figure compared to the current situation. Institutional care systems have their shortcomings, often alienating the elderly from their communities. This paper aims to initiate discussions on alternative approaches, particularly considering ways for the elderly to live within their natural environments. This study was conducted in Lingga Village, Indonesia, through in-depth interviews with 15 elderly individuals and other relevant stakeholders. The findings reveal remarkable narratives about the resilience of the elderly. They are able to maintain their independence due to the support from family members, the presence of their families, and the social roles shaped by their environment. These activities provide a space for the elderly to contribute, allowing them to continue being themselves despite the physical limitations that come with age. In conclusion, this research offers a new perspective on the social landscape approach to anticipating potential negative issues related to elderly life in the future.